EVOLUTION OF MANTLE STRUCTURE BENEATH THE NORTHWEST PACIFIC: EVIDENCE FROM SEISMIC TOMOGRAPHY AND PALEOGEOGRAPHIC RECONSTRUCTIONS - Miller M.S.; Kennett B.L.N. (My University, 2006)
Plate motions and subducting slab morphology are intricately connected, and through the integration of seismicity, tomographic images, and relative plate motions, the evolution of mantle structure can be interpreted. Tomographic images of P wave, shear wave speed, and bulk sound speed perturbations of the northwest Pacific region have been interpreted to define the extent and geometry of the subducting Pacific plate. We have found that the subducted Pacific plate beneath the Japan and Kurile arcs is coherent but is very complex at the junction of the two arcs near the Hokkaido corner, as the slab subduction angle decreases from north to south while the slab thickens. The Pacific slab beneath the Japan arc is slightly thinner and subducting through the upper mantle at a less steep angle than the slab beneath the Kurile arc. As the slab reaches the 660-km discontinuity it becomes stagnant and lies in a horizontal position on top of the transition zone both beneath the Izu and Japan arcs. In contrast, the slab beneath the Kurile arc is subducting at a steeper angle and penetrates through the transition zone into the lower mantle. The difference in slab morphology appears to be due to a combination of change in dip of the subducting plate and the convergence velocity of the Pacific plate along the margin. A new paleogeographic reconstruction of northeast Asia was assembled to evaluate the plate motions that could explain the foundation of the current slab morphology. The plate reconstruction was based on Euler pole motions of the Pacific, Philippine, Amurian, Okhotsk, and North American plates relative to stable Eurasia plate. The new tectonic model illustrates the collision of the Japan and Kurile arcs, the opening of the Kurile Basin, disparity in Pacific plate velocities along the arc, and different rates of trench retreat along the Izu, Japan, and Kurile segments of the western Pacific margin. The plate motion model was interpreted in conjunction with the physical properties of the mantle imaged with the P wave and joint tomography to assess the evolution of the Pacific plate morphology since the mid-Miocene and to provide constraints on the plausible plate motions in the region. Copyright 2006 by the American Geophysical Union.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен